A Systematic Literature Review on Employee Performance through Innovative Work Behavior - Pardomuan Pardosi; Tussi Sulistyowati; Khairil Anwar; Agtovia Frimayasa; Irwin Sukrisno Sugeng (Indonesia Journal of Engineering and Education Technology (IJEET), 2025)
This study employs a qualitative descriptive method through a systematic literature review of 29 empirical studies published between 2018 and 2025, spanning various countries and sectors, to explore how leadership styles influence innovative work behavior (IWB) and employee performance. The findings show that leadership, especially transformational, ambidextrous, relational, and adaptive, significantly enhances IWB, which in turn mediates improvements in employee performance. In addition to leadership, individual factors like creative self-efficacy and work engagement, and organizational aspects such as innovation culture and supportive HR systems, also contribute meaningfully to the development of IWB and performance. Digitalization further enriches this dynamic by facilitating innovation through technology adoption and digital literacy, though its effectiveness depends on moderating factors such as leadership support, psychological safety, and employee digital readiness. These findings indicate a synergistic process in which leadership, organizational culture, individual capability, and digital transformation combine to foster innovation and performance. Implications suggest the need for integrated leadership development, innovation-driven HR practices, and digital capability enhancement. Future research should include longitudinal and cross-cultural designs, consider emerging work patterns like hybrid and remote work, and adopt advanced data analytics to capture the complex interactions among variables shaping IWB and employee outcomes.